Niemann-Pick disease type B. Study of 3 cases and literature revision - Jorge Zarco-Román; Alva Nydia García-Pérez; Paulina Andrade-Aldama; Luis Carbajal-Rodríguez; Raymundo Rodríguez-Herrera (Instituto Nacional de Pediatría, 2014)
Objective: To describe the course of type B Niemann-Pick disease (ENP-B) by following the evolution of three pediatric patients. Methods: Three patients, two of them male, age between two and eleven years, with type B Niemann-Pick disease were evaluated periodically by physic exam and laboratory: hematologic indices, lipid profile, hepatic function tests; Radiologic studies: chest X-ray, abdominal ultrasound, cranial computed tomography, echocardiogram. Histologic exams: hepatic biopsy, bone marrow aspirate. We also obtained information on intercurrent pathologies. Results: Symptoms started at around 3 years (2-5 years) and the diagnosis was made approximately at the age of 5 years 3 months (2-11 years), based on clinical findings suggestive of ENP-B; on foam cells in bone marrow aspirate in the three patients, in hepatic biopsy in two of them and in acid sphingomyelinase determination in three. The coexistent conditions were: hepatosplenomegaly in three; neurologic disorder in two; bone disorder in one; pulmonary disorder in two; liver disorder in three; affected hematological indices in three; lipid abnormalities in three; cardiac involvement in one; ocular manifestations in one; growth retardation in three. In none of the families were detected consanguinity nor endogamy. Conclusions: This study shows the multisystemic character and the clinic variability in the type B Niemann-Pick disease, which is mainly characterized by hepatosplenomegaly and liver dysfunction. Patients have a progressive hypersplenism, atherogenic lipid profile and gradual deterioration of pulmonary function, among other systemic manifestations. To confirm the diagnosis it is required to determine acid sphyngomyelinase. To date, there are no useful biomarkers to evaluate the disease activity. Enzyme replacement therapy is still on research.